Tipologi Kejahatan Perampokan di Indonesia - Prianter Jaya Hairi (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2010)
The robbery cases which being ocurred in Indonesia currently are not just usual type such as house robbery with sharp weapon, but armed robbery with bank as target, jewelry stores, vehicle dealers, and pawnshop. There are many kind of robberies, each typology has a different approach how to overcome it. Therefore, to find a strategy which more responsif and accurate, demand a good comprehension concerning the typology of robbery. The purpose of this study is to find our about typology of robbery in Indonesia. This is library research, which means more deeply anlyze secondary data collected. The data which being search is about general typologies of robbery as well as news and information concerning robbery cases that taken place in Indonesia. Based on the result of the research which had been done, researcher concluding that: First, typology Based on the Occasion, namely robbery based on the target and robbery based on the tactics of the execution all things occured in Indonesia. Second, typology Based on the Offender, namely four general typology of robbery (profesional robbers, opportunist robbers, addict robbers, and alcoholic robbers), alltypes of the robbers are exist in Indonesia. From the invertigation concerning robbery cases in Indonesia, researchcer discover another classification which is not exist in general typologies of robbery, namely: recidivist robbers type, amateur robbers type, aggravated robbers type, and impostor robbers type.